The Effectiveness Of Papaya Peel In Improving Coconut Cooking Oil Quality Based On Northern Kolaka Beliefs - Anry Irawan; Saparuddin Saparuddin; Maretik Maretik; Syahraeni Syahraeni; Shalsa Billa Fausya; Putu Meta Oktaviani (Biodidaktika : Jurnal Biologi dan Pembelajarannya, 2026)
The people of North Kolaka have a unique practice of adding papaya peels during the production of coconut cooking oil. This study aims to evaluate the effect of papaya peel addition on the quality of coconut oil. Coconut oil was produced using four different treatments and evaluated using organoleptic, moisture content, yield, and peroxide value tests. The organoleptic results showed that sample X4 had the most preferred aroma, while sample X3 had the most preferred color. The moisture content of samples X2, X3, and X4 was below the detection limit (